Reproductive strategy as a major factor determining female body size and fertility of a gregarious parasitoid. (14th February 2019) - Samková, Alena; Hadrava, Jiří; Skuhrovec, Jiří; Janšta, Petr
Abstract: The generally known "adult size‐fitness hypothesis" (ASFH) is applied to the gregarious parasitic wasp Anaphes flavipes (Foerster, 1841) (Hymenoptera: Mymaridae). ASFH is dependent on the reproductive strategy of the mother, which means the larger females have more offspring compared to smaller females. Two main factors, the mother's body size and food quantity received during larval development, can affect the body size of the offspring. For the first time, we present a study on the relative effect of both factors on fitness of the same species, wasp A. flavipes . Our data confirmed that females of A. flavipes with larger body sizes had more offspring compared to smaller ones. At the same time, mother's body size does not seem to affect the body size of the offspring. The other studied factor, quantity of food received during larval development, can be influenced by reproductive strategy (number of parasitoids developing in one host egg), host quality or the duration of development. We found only the reproductive strategy to have a statistically significant effect on body size. We demonstrated that the variable reproductive strategy (VRS) of wasp A. flavipes causes a plasticity in body size and future number of offspring. The generally known "trade‐off" scheme (more small offspring or fewer bigger offspring) does not apply to A. flavipes, because their large females have more offspring and it is their reproductive strategy that determines body size.